Salvaging the image of the N'Dama breed: productivity evidence from village production systems in The Gambia - Agyemang, K.; Little, D.A.; Dwinger, R.H. (International Laboratory for Research on Animal Diseases, 1994)
This paper summarises the productivities of N'Dama cattle in traditional production systems inthe Gambia and describes the responses in productivity achieved when nutritional interventions were applied. The studies were carried out at six sites where herd management patterns are similar. Cattle are released in the morning after milk extraction for grazing. Calves are allowed to graze around the tethering sites . During the dry season, animals roam freely. Milk offtake for human consumption was measured for individual cows once a month, starting one to two weeks after calving, and up to weaning of the calf. Cow and calf liveweights were also measured. From these data age at first calving, calving interval, calf weaning weight, weight at 12 months, growth rate, viability, body weight, lactation length and milk offtake were calculated. Performance traits were analysed. Factors investigated were herd, parity of cow, year and season of calving, or birth and sex of calf. The results of this study have demonstrated that when milk extracted from N'Dama for human consumption was taken into consideration, the overall productivity was superior to that of Zebu breeds maintained under similar traditional but tsetse-free systems. Nutritional supplementation to reduce the constraints of seasonal feed shortages could result in major increase in productivity.